MG1-1995959: An Eclipsing Binary Star with a Pronounced O’Connell Effect - Eric R. Craine; Brian L. Craine; Christopher J. Corbally; Adam L. Kraus; Andy S. Kulessa; Roger B. Culver; Grady Boyce; Tim B. Hunter; W. Marwood; Mike Miller; Geoffrey C. Stone (The Astrophysical Journal)
MG1-1995959 is a short-period (∼0.586 day) eclipsing binary, exhibiting at times an extraordinarily large O’Connell effect (OE), for which this paper reports its discovery, time series photometry, and spectroscopic observation. The photometry is scattered across years 2001–2023, with spectroscopic observations from 2023. Photometric curves exhibit classical OE asymmetries, whereby maxima following primary and secondary eclipses are of different magnitudes. Short time span photometric time series provide static characterizations of OE stars yielding incomplete representations of critical macrobehavior. In contrast, MG1-1995959 photometry is of sufficient duration to indicate pronounced changes in such behavior, suggesting that intense observing programs can provide key benchmark data to better inform complex modeling efforts. Spectra indicate the primary to be K1 Vk(e), and the secondary type is ∼K5 V. PHOEBE modeling of the light curve from 2014 enables estimation of key stellar parameters (primary/secondary): T _eff [K] (5110/4260), and, in solar units, mass (0.86/0.68) and radius (0.93/0.65). The inclination of the system was found to be ∼78°. PHOEBE modeling of light curves from 2013, 2022, and 2023 is presented, demonstrating (1) the light curves can be well fit by invoking distributions of star spots, (2) optimal spot sizes and distributions vary dramatically as a function of time, and (3) this is a powerful tool with which to investigate the short term evolution of this star. MG1-1995959 is an accessible star with dynamic and unusual behavior deserving of intensive study to better understand nuances of the OE and the nature of late-type main-sequence stars.